Raḍā’ah in Islamic Psychological Perspective - Hasanusi, Harmathilda (Universitas Muhammadiyah Yogyakarta, 2022)
This paper studied Islam & Psychology’s view of the concept of raḍā’ah, which has been proven to provide many benefits. There are 28 verses in the Qur’an that discuss raḍā’ah. In general, this is seen as a natural female activity with children. Accordingly, the command for mothers to breastfeed their children is stated in surah Al-Baqarah (2) Verse 233. Similarly, Surah At-Talaq (65) verse 6 also explains the importance of breastfeeding, which, even if forced to be breastfed by others, is allowed by giving money to the breastfeeding mother. ASI (breast milk) is the best food that contains all the nutrients needed by 0 - 6 months old babies. It directly affects the baby's growth, including mental and emotional development, through the bonding between mother and child when breastfeeding. Lack of attachment between mother and baby may lead to mental-emotional disorders that hinder the child’s development. Breast milk contains immunological substances. Packaged milk actually contains bacteria as a result of processing and packaging that can be harmful to a baby’s health. Breastfeeding also increases children’s intelligence courtesy of the nutritional content of breast milk, the direct method of giving from the mother's touch to the baby, as well as the duration of breastfeeding.